2010
DOI: 10.1074/jbc.m109.095075
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis AtSerpin1, Crystal Structure and in Vivo Interaction with Its Target Protease RESPONSIVE TO DESICCATION-21 (RD21)

Abstract: In animals, protease inhibitors of the serpin family are associated with many physiological processes, including blood coagulation and innate immunity. Serpins feature a reactive center loop (RCL), which displays a protease target sequence as a bait. RCL cleavage results in an irreversible, covalent serpin-protease complex. AtSerpin1 is an Arabidopsis protease inhibitor that is expressed ubiquitously throughout the plant. The x-ray crystal structure of recombinant AtSerpin1 in its native stressed conformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 74 publications
2
95
0
1
Order By: Relevance
“…S4). Similar results have been described by Lampl et al (13) and were shown to be a result of cleavage of AtSerpin1 in the RCL. When cysteine protease inhibitors such as E-64, leupeptin, and antipain were coinfiltrated with DCG-04, neither the upper nor the lower AtSerpin1 bands appeared.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…S4). Similar results have been described by Lampl et al (13) and were shown to be a result of cleavage of AtSerpin1 in the RCL. When cysteine protease inhibitors such as E-64, leupeptin, and antipain were coinfiltrated with DCG-04, neither the upper nor the lower AtSerpin1 bands appeared.…”
Section: Resultssupporting
confidence: 80%
“…When the seedlings begin to de-etiolate, RD21 is released from the complex to counteract digestive proteases in the arthropod gut, conferring efficient protection (16). In greening and mature seedlings, RD21 is operative as a prodeath factor that triggers programmed host cell death once released from the vacuole (13,14). Binding of RD21 to AtSerpin1, however, is a mechanism to control RD21's activity as prodeath factor (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations